Electrochemical device

By using polymer fiber base film and vinylene carbonate electrolyte in lithium-ion batteries, the adhesion between the separator and the negative electrode sheet is improved, and the problems of battery expansion and safety hazards are solved, and higher cycle life and energy density are achieved. .

CN119275495APending Publication Date: 2025-01-07ZHUHAI COSMX POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362164.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the circulation process, existing lithium-ion batteries have problems such as reducing the adhesion force between the diaphragm and the negative electrode sheet, which increases the expansion of the battery, which has a high safety hazard, and the increase in the thickness of the battery cell leads to a decrease in energy density.

Method used

A separator containing a base film, an inorganic particle layer and a glue coating layer is used. The base film contains polymer fibers. Vityl carbonate is added to the electrolyte solution to increase the adhesion between the separator and the negative electrode sheet by hot pressing, and it is formed when the battery is melted. SEI film enhances the adhesion between the diaphragm and the negative electrode sheet.

Benefits of technology

It improves the cycle life of the battery, reduces the cycle expansion, enhances the hardness and safety performance of the battery, and improves the process yield and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275495A_ABST
    Figure CN119275495A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and provides an electrochemical device, the electrochemical device comprises an electrolyte and a battery cell, the battery cell comprises a negative plate, a diaphragm and a positive plate, the diaphragm comprises a base film, an inorganic particle layer and a gluing layer which are sequentially arranged along the direction from the negative plate to the positive plate, and the base film comprises polymer fibers; the electrolyte comprises vinylene carbonate; the electrochemical device satisfies: 0.33 < = 10G / C < = 13.3; wherein the total length of the polymer fibers is C [mu] m on the surface, facing the negative electrode, of the base film per square micron; the mass content of vinylene carbonate in the electrolyte is G wt%; wherein the tensile strength of the base film in the TD direction is greater than 200Kgf / cm < 2 >. According to the electrochemical device, the bonding performance between the diaphragm and the negative plate and the safety performance of the battery can be improved while relatively high energy density is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrochemical device. Background Art

[0002] In recent years, as lithium-ion batteries have been widely used in fields such as smartphones, laptops, power tools and electric vehicles, consumers' performance requirements for the above products have continued to increase, which requires batteries to have longer service life, better charging and discharging performance and safety performance in terms of cycle performance.

[0003] At present, there are still safety hazards in the use of batteries. For example, after multiple charge and discharge cycles, the battery will expand in thickness, which can easily cause fire or even explosion. The main reason for the above safety issues is that as the number of battery charge and discharge cycles increases, the adhesion between the battery separator and the negative electrode sheet decreases, making the negative electrode side of the battery more likely to expand during use, which in turn causes the interface between the separator and the electrode sheet to deteriorate, causing safety issues.

[0004] In addition, the diaphragms used in large quantities in the lithium battery industry are those coated with PVDF glue on the base film surface of the diaphragm. This type of glue has weak adhesion to the negative electrode sheet, and the adhesion of the PVDF glue is further reduced after the electrolyte swells, resulting in the problem of softening the battery cell. Softened batteries are more likely to have abnormalities such as edge ridges and large expansion during the cycle process, posing a safety hazard. In addition, after the base film surface is sprayed with PVDF glue, the thickness of the diaphragm is further increased, which in turn leads to an increase in the thickness of the battery cell, resulting in problems such as a decrease in the volume energy density of the battery cell. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide an electrochemical device which can improve the bonding performance between the diaphragm and the negative electrode sheet while ensuring a higher energy density, thereby improving the hardness of the battery cell, and at the same time alleviate battery expansion to improve the safety performance of the battery.

[0006] In order to achieve the above object, the present invention provides an electrochemical device, the electrochemical device comprises an electrolyte and a battery cell, the battery cell comprises a negative electrode sheet, a separator and a positive electrode sheet, and in the direction from the negative electrode sheet to the positive electrode sheet, the separator comprises a base film, an inorganic particle layer and a coating layer arranged in sequence, the base film comprises polymer fibers; the electrolyte comprises vinylene carbonate; the electrochemical device satisfies:

[0007] 0.33≤10G / C≤13.3;

[0008] Wherein, the total length of the polymer fibers on the surface of the base film facing the negative electrode per square micron is C μm;

[0009] Among them, the tensile strength of the base film in TD direction is > 200Kgf / cm 2 ;

[0010] The mass content of vinylene carbonate in the electrolyte is G wt %.

[0011] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0012] The present invention uses a base film with relatively large tensile strength in the TD direction, which has good processability, can improve the bonding force between the base film and the positive electrode after hot pressing, and improve the battery process yield. On this basis, vinylene carbonate (VC) is added to the synergistic electrolyte, and its content and the total length of the polymer fiber in the base film are controlled to meet the above formula, which can further improve the bonding force between the diaphragm and the negative electrode after hot pressing, and further improve the battery process yield; during battery formation, an SEI film can be formed between the diaphragm base film and the negative electrode, further improving the bonding force between the diaphragm base film surface and the negative electrode, and making the bonding force relatively stable during the use of the battery, thereby improving the interface performance between the diaphragm and the negative electrode during the charge and discharge process of the battery cell, achieving the purpose of increasing the cycle life of the battery cell and reducing cycle expansion, while improving the safety performance of the battery.

[0013] Moreover, when the rubber coating layer of the diaphragm is in contact with the positive electrode, there is also bonding force between the two. The existence of bonding force between the positive electrode and the diaphragm and between the negative electrode and the diaphragm can effectively improve the hardness of the battery cell, increase the degree of integration between the electrode and the diaphragm, and the battery cell can remain in a non-fluffy state during welding and assembly, thereby improving the process yield.

[0014] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Shown is a schematic diagram of a battery cell in some embodiments of the present invention.

[0016] Figure 2 Shown is a SEM image of the surface of the inorganic particle layer in the present invention after being processed by ImageJ software.

[0017] Figure 3 Shown is a SEM image of the surface of the basement membrane facing the negative electrode in the present invention processed by ImageJ software.

[0018] Figure 4 Shown is a SEM image of the surface of the basement membrane facing the negative electrode in the present invention processed by ImageJ software.

[0019] Figure 5 Shown is a schematic diagram of a three-point hardness test of a battery cell in the present invention.

[0020] Figure 6 Shown is a picture of the battery cell after three-point hardness test in the present invention.

[0021] Description of Reference Numerals

[0022] 1 is a separator, 3 is a negative electrode sheet, 2 is a positive electrode sheet, 11 is a glue layer, 12 is an inorganic particle layer, 13 is a base film; 0 is a battery cell, Z1 and Z2 are support rollers, and PG is a pressure roller. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0025] In the separator of the battery in the present invention, a coating is applied on one side of the base film, which reduces the thickness of the separator, can reduce the thickness of the battery cell, and then improve the volume energy density of the battery cell. However, in this case, the bonding force between the separator and the negative electrode sheet will be reduced, which will lead to a low yield of the battery process, and the cycle performance and life are also greatly reduced. It has been found that by adding vinylene carbonate (VC) to the electrolyte and controlling its content to meet a certain relationship with the total length of the polymer fiber in the base film, a SEI film can be formed between the separator base film and the negative electrode sheet during battery formation. The SEI film is formed on the negative electrode sheet and extends to the polymer fibers on the separator base film surface. It can improve the bonding force between the separator base film surface and the negative electrode sheet, and the bonding force remains substantially undecayed during the battery charging and discharging process, thereby improving the interface performance between the separator and the negative electrode sheet during the battery charging and discharging process, and achieving the purpose of improving the battery cell cycle life and reducing cycle expansion. The adhesive force between the adhesive layer on the other side of the diaphragm and the positive electrode can reach 5N / m. This adhesive force mainly comes from the adhesive force between the diaphragm adhesive layer and the positive electrode under a certain pressure after the adhesive layer reaches the glass transition temperature. The existence of the above adhesive force can effectively improve the hardness of the battery cell, increase the degree of integration between the electrode and the diaphragm, and keep the battery cell in a non-fluffy state during welding and assembly, thereby improving the process yield.

[0026] The present invention provides an electrochemical device, comprising an electrolyte and a battery cell, wherein the battery cell comprises a negative electrode sheet, a separator and a positive electrode sheet, and in a direction from the negative electrode sheet to the positive electrode sheet, the separator comprises a base film, an inorganic particle layer and a coating layer arranged in sequence, wherein the base film comprises polymer fibers; the electrolyte comprises vinylene carbonate; and the electrochemical device satisfies:

[0027] 0.33≤10G / C≤13.3;

[0028] Wherein, the total length of the polymer fibers on the surface of the base film facing the negative electrode per square micron is C μm;

[0029] Among them, the tensile strength of the base film in TD direction is > 200Kgf / cm 2 ;

[0030] The mass content of vinylene carbonate (VC) in the electrolyte is G wt %.

[0031] In some embodiments, the electrochemical device comprises an electrolyte and a battery cell, the battery cell comprises a negative electrode sheet 3, a separator 1 and a positive electrode sheet 2, and along the direction from the negative electrode sheet 3 to the positive electrode sheet 2, the separator comprises a base film 13, an inorganic particle layer 12 and a coating layer 11 arranged in sequence, that is, one side of the base film 13 is adjacent to the negative electrode sheet 3, and the coating layer 11 is adjacent to the positive electrode sheet 2, for example Figure 1 shown.

[0032] In some embodiments, 6≤C≤15, such as 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, the basement membrane fibers that meet the design have uniform pores and high tensile strength. C can be obtained by measuring the fibers on the SEM image and statistically calculating them using ImageJ software. For example, a 1 square micron size is selected on the SEM image, marked along the length direction of the polymer fiber, and then the total length of the polymer fiber is calculated. Figure 4 Perform test calculations as shown.

[0033] In some embodiments, 0.5≤G≤8, such as 0.3, 0.5, 1.5, 2.0, 2.5, 3, 4, 6, 8, 10. The G value is related to the formation of SEI film on the negative electrode sheet of the battery. The higher the content, the thicker the SEI film is formed and the more stable the interface is. When the content of vinylene carbonate is within this range, the bonding force between the negative electrode sheet and the separator can be further improved, thereby improving the cycle performance and life of the battery; however, when the content is too high, the internal resistance of the battery is too high.

[0034] In some embodiments, the inorganic particle layer contains inorganic particles, and there may be holes between the inorganic particles. The area ratio of the holes between the inorganic particles is A, 0.1≤A≤0.25. In the present invention, the SEM image of the surface or interior of the inorganic particle layer of the diaphragm (the surface of the inorganic particle layer can be selected for ease of observation) can be measured and the hole ratio can be counted by ImageJ software. ImageJ software processing method: import the SEM image, then process the SEM image through ImageAdjustThreshold, and then distinguish the inorganic particles from the holes through the Wekatrain process, and then calculate the hole area ratio, for example Figure 2 As shown, the white area is the inorganic particles and the black area is the pores. The smaller the A value, the smaller the pores between the inorganic particles, and the lower the ability of the inorganic particle layer of the separator to retain the electrolyte; the larger the A value, the higher the ability of the inorganic particle layer of the separator to retain the electrolyte.

[0035] It should be understood that, whether it is the measurement and statistical process of A or B, the entire surface of the sample can be measured. In order to reduce the workload and obtain relatively accurate values ​​at the same time, multiple sites on the surface of the sample to be measured can be selected, and regions with a certain area (for example, 1 square micron, 2 square microns, 5 square microns) can be intercepted from the SEM image at multiple locations, and the average value of the area ratio of multiple regions can be used as the measurement value.

[0036] In some embodiments, the inorganic particle layer comprises inorganic particles, and there are pores between the inorganic particles. The area ratio of the pores between the inorganic particles on the surface of the inorganic particle layer is A, and 0.1≤A≤0.25.

[0037] In some embodiments, the inorganic material comprises at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and nickel oxide.

[0038] In some embodiments, the Dv50 of the inorganic particles is 0.05 μm-3 μm, and the Dv90 is 0.3 μm-6 μm. Inorganic particles within this size range have obvious advantages in absorbing electrolyte in batteries. When the inorganic particles are smaller in size, the weight per unit volume increases, reducing the battery energy density, and the pore size between particles decreases, which significantly reduces the amount of electrolyte retained; when the inorganic particles are larger in size, the thickness of the diaphragm increases, and the consistency of the diaphragm thickness decreases, which has an adverse effect on battery performance.

[0039] In the present invention, the particle size of the inorganic particles can be measured by a particle size analyzer.

[0040] In some embodiments, pores are formed between polymer fibers on the surface of the base membrane facing the negative electrode, and the area ratio of the pores between polymer fibers per unit area is B, 0.15≤B≤0.4, such as 0.15, 0.2, 0.25, 0.3, 0.35, 0.4. The SEM image of the surface of the base membrane of the diaphragm can be measured and the hole ratio can be counted by ImageJ software. ImageJ software processing method: import the SEM image, then process the SEM image through ImageAdjustThreshold, and then distinguish the polymer fibers from the pores through the Wekatrain process, and then calculate the area ratio, for example Figure 3 As shown in the figure, the white area is the polymer fiber, and the black part is the hole between the polymer fibers. The smaller the B value, the higher the proportion of polymer fiber area, the larger the contact area between the polymer fiber and the negative electrode sheet, and the greater the adhesion between the separator and the negative electrode sheet after the battery is formed; the larger the B value, the lower the proportion of polymer fiber area, the smaller the contact area between the polymer fiber and the negative electrode sheet, and the lower the adhesion.

[0041] In some embodiments, 0.3≤BG / A≤12, for example, it can be 0.3, 0.5, 1, 2, 4, 6, 8, 10, 12. When BG / A is within this range, it is beneficial to maintain the adhesion between the diaphragm and the negative electrode sheet in an appropriate range after formation, thereby improving the interface performance between the diaphragm and the negative electrode sheet during the charge and discharge process of the battery cell, thereby achieving the purpose of increasing the cycle life of the battery cell and reducing cycle expansion.

[0042] In some embodiments, the coating layer comprises a polymer, and the polymer comprises at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid resin, polymethyl acrylate, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, ethylene-acrylic acid copolymer, polyethyl acrylate and sodium carboxymethyl cellulose.

[0043] In some embodiments, the polymer comprises butyl acrylate-acrylonitrile copolymer.

[0044] In some embodiments, the thickness of the base film is 5 μm-12 μm. When the base film thickness is kept within this range, the VC retention in the separator increases with the increase in the base film thickness, and VC can be stably provided during the cycle to repair the interface film damage caused by volume expansion, while maintaining a relatively stable bonding force between the negative electrode sheet and the separator, thereby extending the cycle life of the battery.

[0045] In some embodiments, the thickness of the inorganic particle layer is 0.5 μm-4 μm. When the thickness of the inorganic particle layer is kept within this range, the increase in the thickness of the inorganic particle layer not only helps to increase the VC content in the separator, but also reduces the thermal shrinkage of the separator during use, thereby improving the safety performance of the battery.

[0046] In some embodiments, the thickness of the adhesive layer is 0.5 μm-6 μm. When the thickness of the adhesive layer is kept within this range, it is beneficial to improve the bonding force between the adhesive layer and the positive electrode sheet, which helps to improve the hardness of the battery cell, thereby improving the process yield of the battery.

[0047] In some embodiments, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises graphite. The graphite may be natural graphite and / or artificial graphite.

[0048] In some embodiments, the negative electrode active material further comprises a silicon-based material. Silicon-doped negative electrode sheets can have higher rate performance and energy density, and are more suitable for improving the fast charging performance of the battery. However, such negative electrode sheets have weak adhesion to the diaphragm, resulting in such batteries having problems such as large volume expansion during the cycle and low residual capacity during storage, which can be improved by the solution described in the present invention.

[0049] In some embodiments, the negative electrode active material further comprises a carbon-based material other than graphite, such as at least one of hard carbon, carbon nanotubes, graphene, etc. Negative electrodes doped with other carbon materials can have higher rate performance and energy density, but such negative electrodes have weak adhesion to the separator, resulting in such batteries being prone to expansion during the cycle and causing rapid capacity decay, which can be improved through this design.

[0050] In some embodiments, the carbon material other than graphite comprises at least one of soft carbon, hard carbon, and graphene.

[0051] In some embodiments, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder.

[0052] In some embodiments, the negative electrode active material layer comprises 80-99.8 wt % of a negative electrode active material, 0.1-10 wt % of a negative electrode conductor, and 0.1-10 wt % of a negative electrode binder.

[0053] In some embodiments, the negative electrode active material layer comprises 90-99.6 wt % of a negative electrode active material, 0.2-5 wt % of a negative electrode conductor, and 0.2-5 wt % of a negative electrode binder.

[0054] In one embodiment, the negative electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.

[0055] In one embodiment, the negative electrode binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0056] The negative electrode current collector may be a negative electrode current collector commonly used in the art, such as copper foil or a composite current collector.

[0057] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0058] In some embodiments, the positive electrode active material comprises a lithium composite oxide.

[0059] In some embodiments, the chemical formula of the positive electrode active material includes LiFe 1-d-e M d N e PO4, wherein 0≤d≤0.1, 0≤e≤0.05, M includes at least one of Mn and Al, and N includes at least one of Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce and Te.

[0060] In some embodiments, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0061] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of positive electrode conductive agent, and 0.1-10wt% of positive electrode binder.

[0062] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of positive electrode conductive agent, and 0.2-5wt% of positive electrode binder.

[0063] In some embodiments, the positive electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0064] In some embodiments, the positive electrode binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0065] In some embodiments, the positive electrode current collector may be a positive electrode current collector conventionally used in the art, such as aluminum foil or a composite current collector.

[0066] In some embodiments, the electrolyte further comprises a lithium salt, an organic solvent and a functional additive.

[0067] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, or lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate (LiBF4), lithium bis(difluorophosphoryloxy)difluoroborate, and lithium tetrakis(difluorophosphoryloxy)borate.

[0068] In some embodiments, the organic solvent comprises carbonate and / or carboxylate.

[0069] In some embodiments, the organic solvent includes but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl butyrate (MB), ethyl butyrate (EB), ethyl acetate (EA), propyl acetate (PA), etc.

[0070] In some embodiments, the functional additive comprises at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), propene sultone (PST), methylene disulfonate (MMDS), 1,3-propane sultone (PS), vinyl sulfate (DTD), divinyl sulfate (BiDTD), tetravinylsilane (TVS), tris(trimethylsilyl)borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), pentafluoroethoxycyclotriphosphazene (PFPN), and the like.

[0071] In some embodiments, the lithium salt accounts for 12wt%-25wt% of the total mass of the electrolyte, for example, it can be 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, or 25wt%.

[0072] In some embodiments, the organic solvent accounts for 50wt%-80wt% of the total mass of the electrolyte, for example, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 80wt%.

[0073] In some embodiments, the added amount of the functional additive is 8wt%-25wt% of the total mass of the electrolyte, for example, it can be 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%.

[0074] In some embodiments, the electrochemical device is a lithium-ion battery.

[0075] In some embodiments, the electrochemical device may further include a shell that wraps the battery cell, and the shell may be made of, for example, an aluminum-plastic film.

[0076] If not otherwise specified, other options for the electrochemical device are conventional options in the art, and the assembly method thereof can be performed in a conventional manner in the art.

[0077] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0079] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0080] Example 1 and Comparative Example 1

[0081] (1) Preparation of positive electrode

[0082] The positive electrode active material (LiFePO4), the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are mixed in a weight ratio of 96.5:2:1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the aluminum foil current collector; the coated aluminum foil is baked in an oven with different temperature gradients, and then dried in an oven at 100°C for 8 hours, and then rolled and cut to obtain the desired positive electrode sheet.

[0083] (2) Preparation of negative electrode sheet

[0084] The negative electrode active material artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, acetylene black, and single-walled carbon nanotubes (SWCNT) are mixed in a weight ratio of 95.9:1:2:1:0.1, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on a copper foil current collector; and the negative electrode sheet is obtained by drying in an oven at 85°C for 5h, rolling and die-cutting.

[0085] (3) Preparation of diaphragm

[0086] 7μm thick polyethylene film (TD tensile strength > 200Kgf / cm2) prepared by wet process 2 ), and then coat a 2μm thick alumina coating on one side of the base membrane (the Dv50 of the alumina particles is 0.8μm, the Dv90 is 1.8μm, and there are pores between adjacent alumina particles), and then coat polyvinylidene fluoride resin on the surface of the alumina coating, and then dry and cut to obtain the finished diaphragm.

[0087] (4) Preparation of electrolyte

[0088] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 25:5:20:50, and LiPF6 (14wt% based on the total mass of the electrolyte) and different contents of vinylene carbonate VC were slowly added to the mixed solution and stirred to obtain an electrolyte.

[0089] (5) Preparation of lithium-ion batteries

[0090] The above-mentioned positive electrode sheet, separator and negative electrode sheet are stacked to obtain a bare battery cell. During the stacking process, the separator base film faces the negative electrode sheet and the other side faces the positive electrode sheet. The battery cell is then hot-pressed, welded and packaged to prepare a dry battery cell. After baking, liquid injection, standing, formation, degassing molding, sorting and other processes, a lithium-ion battery is obtained.

[0091] The area ratio of pores formed between alumina particles on the surface of the alumina coating is A; the area ratio of pores formed between polymer fibers on the surface of the base membrane facing the negative electrode is B; the total length of polymer fibers per square micron on the surface of the base membrane facing the negative electrode is C μm; the mass content of vinyl carbonate in the electrolyte is G wt%; and 10G / C and GB / A are calculated. The specific values ​​of the above parameters and the tensile strength of the base membrane in the TD direction are shown in Table 1.

[0092] The battery cells of Examples 1-4 were subjected to hot pressing treatment using the parameters of 85°C, 5 MPa, and 180 s, and then the adhesion between the battery separator and the negative electrode sheet of the battery cells was tested respectively. The test samples were cut into a width of 15 mm and the adhesion was tested by a universal tensile testing machine. The test results are shown in Table 2.

[0093] Comparative Example 2

[0094] The operation was carried out according to the method described in Example 1-3, except that the base film was a polypropylene base film, and its TD tensile strength was 128 Kgf / cm 2 .

[0095] Example 2 Group

[0096] The method described in Examples 1-3 was followed, except that the particle sizes of the ceramic particles were controlled to produce diaphragms of different specifications. The area percentages A of the pores formed between the ceramic particles of the diaphragm used in the lithium-ion battery were different, as shown in Table 1.

[0097] Example 3 Group

[0098] The operation is carried out according to the method described in Examples 1-3, except that the porosity of the base membrane is controlled to be different so that the area ratio of the pores between the polymer fibers on the base membrane is different, that is, B is different, and C also varies with B, as shown in Table 1.

[0099] Example 4 and Comparative Example 3

[0100] The operation is carried out in accordance with the method described in Examples 1-3, except that the porosity of the base membrane is controlled to be different so that the area ratio of the pores between the polymer fibers on the base membrane is different, that is, B is different, and C also varies with B; ceramics of different particle sizes are used for coating to prepare diaphragms with different A values; and then electrolytes with different G contents are used, as shown in Table 1.

[0101] Table 1

[0102] serial number A B C G 10G / C GB / A <![CDATA[Tensile strength of TD Kgf / cm 2 > Comparative Example 1-1 * * * 0 0 0 * Comparative Example 1-2 * * * 0.3 0.29 0.43 * Example 1-1 0.19 0.27 10.40 0.5 0.48 0.71 1580 Example 1-2 * * * 1.5 1.44 2.13 * Examples 1-3 * * * 2.5 2.40 3.55 * Examples 1-4 * * * 4.0 3.85 5.68 * Examples 1-5 * * * 6.0 5.77 8.53 * Examples 1-6 * * * 8.0 7.69 11.37 * Examples 1-7 * * * 9.0 8.65 12.79 * Comparative Example 2 0.20 0.25 11.25 2.5 2.22 3.13 128 Example 2-1 0.08 0.25 11.20 2.5 2.23 7.81 1456 Example 2-2 0.10 ** ** ** ** 6.25 ** Example 2-3 0.14 ** ** ** ** 4.46 ** Embodiment 2-4 0.16 ** ** ** ** 3.91 ** Embodiment 2-5 0.18 ** ** ** ** 3.47 ** Embodiment 2-6 0.20 ** ** ** ** 3.13 ** Embodiment 2-7 0.22 ** ** ** ** 2.84 ** Embodiment 2-8 0.25 ** ** ** ** 2.50 ** Embodiment 2-9 0.28 ** ** ** ** 2.23 ** Example 3-1 * 0.12 15.30 * 1.63 1.58 1280 Example 3-2 * 0.16 14.80 * 1.69 2.11 1334 Example 3-3 * 0.20 13.00 * 1.92 2.63 1382 Embodiment 3-4 * 0.25 10.30 * 2.43 3.29 1456 Embodiment 3-5 * 0.28 10.20 * 2.45 3.68 1523 Embodiment 3-6 * 0.30 9.50 * 2.63 3.95 1588 Embodiment 3-7 * 0.34 8.80 * 2.84 4.47 1625 Embodiment 3-8 * 0.40 7.20 * 3.47 5.26 1673 Embodiment 3-9 * 0.45 5.80 * 4.31 5.92 1688 Example 4-1 0.25 0.20 13.20 0.50 0.38 0.40 1388 Example 4-2 0.22 0.25 10.30 1.50 1.46 1.70 1465 Example 4-3 0.20 0.28 10.20 2.50 2.45 3.50 1562 Example 4-4 0.18 0.30 9.10 4.00 4.40 6.67 1622 Embodiment 4-5 0.16 0.34 8.20 6.00 7.32 12.75 1634 Embodiment 4-6 0.14 0.40 7.10 8.00 11.27 22.86 1682 Comparative Example 3-1 0.28 0.16 14.40 0.30 0.21 0.17 1343 Comparative Example 3-2 0.10 0.45 5.30 9.00 16.98 40.50 1700

[0103] Note: * indicates the same as Example 1-1, ** indicates the same as Example 2-1.

[0104] Test Case

[0105] The performance of the batteries prepared in the examples and comparative examples was tested, and the specific results are shown in Table 2.

[0106] (1) Cycle performance test: At 25°C and 45°C, the lithium-ion battery was charged to full charge at 1.0C with a cut-off current of 0.02C and left to stand for 3 min. It was then discharged to 2.5V at 1.0C and left to stand for 3 min. After 500 cycles, the capacity retention rate and battery expansion rate were tested.

[0107] Among them, capacity retention rate = discharge capacity / initial capacity×100%, battery expansion rate = (full-charged battery thickness-battery initial thickness) / battery initial thickness×100%.

[0108] (2) Cell hardness test: Take the cells of each group mentioned above and perform a three-point hardness test on the cells at 25°C. The three points refer to the contact positions between the pressure roller PG, the support roller Z1 and the support roller Z2 and the cells. The schematic diagram is shown in the figure. Figure 5 As shown, the two support rollers Z1 and Z2 are located below the battery cell near the two ends, and the pressure roller is located above the middle of the battery cell, and the distance between the support rollers Z1 and Z2 is basically the same. The test result is the pressure change value during the pressure roller stroke of 2.5mm, and the output value is the maximum pressure value during the pressure roller PG stroke of 2.5mm, which is recorded as the battery cell hardness. Figure 6 Shown is a picture of a battery cell after a three-point hardness test.

[0109] Table 2

[0110]

[0111]

[0112] The lithium-ion battery of the present invention uses a base film with high tensile strength in the TD direction, and by controlling the total length C of the polymer fiber on the base film surface and the mass content of vinyl carbonate to meet a certain relationship, the bonding force between the negative electrode sheet and the base film surface of the separator can be increased after hot pressing, thereby improving the hardness of the battery cell and improving the yield of the battery cell process. At the battery level, since the bonding force between the polymer fiber on the base film surface of the battery separator and the negative electrode sheet does not decay with the battery charging and discharging, the expansion rate during the battery cycle is well controlled, thereby improving the battery cycle capacity retention rate and battery safety performance.

[0113] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrochemical device, characterized in that: The electrochemical device comprises an electrolyte and a battery cell, wherein the battery cell comprises a negative electrode sheet, a separator and a positive electrode sheet, and in a direction from the negative electrode sheet to the positive electrode sheet, the separator comprises a base film, an inorganic particle layer and a coating layer arranged in sequence, wherein the base film comprises polymer fibers; the electrolyte comprises vinylene carbonate; and the electrochemical device satisfies: 0.33≤10G / C≤13.3; Wherein, the total length of the polymer fibers on the surface of the base film facing the negative electrode per square micrometer is C μm; the mass content of vinylene carbonate in the electrolyte is G wt%; Among them, the tensile strength of the base film in TD direction is > 200Kgf / cm 2 .

2. The electrochemical device according to claim 1, characterized in that 6≤C≤15; and / or 0.5≤G≤8。 3. The electrochemical device according to claim 1 or 2, characterized in that: The inorganic particle layer comprises inorganic particles, there are pores between the inorganic particles, the area ratio of the pores between the inorganic particles is A, and 0.1≤A≤0.25; and / or Pores are formed between the polymer fibers on the surface of the base film facing the negative electrode, and the area ratio of the pores between the polymer fibers is B; 0.15≤B≤0.

4.

4. The electrochemical device according to claim 3, characterized in that 0.3≤BG / A≤12.

5. The electrochemical device according to claim 3, characterized in that The inorganic material comprises at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide and nickel oxide; and / or The Dv50 of the inorganic particles is 0.05μm-3μm, and the Dv90 is 0.3μm-6μm.

6. The electrochemical device according to any one of claims 1 to 5, characterized in that: The thickness of the base film is 5 μm-12 μm; and / or The thickness of the inorganic particle layer is 0.5 μm-4 μm; and / or The thickness of the adhesive layer is 0.5 μm-6 μm.

7. The electrochemical device according to any one of claims 1 to 6, characterized in that: The coating layer comprises a polymer, and the polymer comprises at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid resin, polymethyl acrylate, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, ethylene-acrylic acid copolymer, polyethyl acrylate and sodium carboxymethyl cellulose.

8. The electrochemical device according to any one of claims 1 to 7, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises graphite; Preferably, the negative electrode active material further comprises a silicon-based material; Preferably, the negative electrode active material further comprises a carbon-based material other than graphite, and the carbon-based material other than graphite is selected from at least one of hard carbon, carbon nanotubes, and graphene.

9. The electrochemical device according to any one of claims 1 to 8, characterized in that: The bonding force between the glue coating layer and the positive electrode sheet reaches more than 5N / m.

10. The electrochemical device according to any one of claims 1 to 9, characterized in that: The electrochemical device is a lithium ion battery.